2021
DOI: 10.1080/15563650.2021.1893742
|View full text |Cite
|
Sign up to set email alerts
|

Methadone and suboxone® mentions on twitter: thematic and sentiment analysis

Abstract: Background: According to the latest medical evidence, Methadone and buprenorphine-naloxone (Suboxone V R ) are effective treatments for opioid use disorder (OUD). While the evidence basis for the use of these medications is favorable, less is known about the perceptions of the general public about them.Objective: This study aimed to use Twitter to assess the public perceptions about methadone and buprenorphine-naloxone, and to compare their discussion contents based on themes/topics, subthemes, and sentiment. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 24 publications
(26 reference statements)
0
14
0
2
Order By: Relevance
“…A total of 15 905 182 substance‐related social media posts (15 804 353 text posts, 68 023 image posts, and 32 470 video posts) were assessed across all 73 studies. Twitter data was analysed in 34 studies [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ]; 23 studies examined YouTube [ 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , ...…”
Section: Resultsmentioning
confidence: 99%
“…A total of 15 905 182 substance‐related social media posts (15 804 353 text posts, 68 023 image posts, and 32 470 video posts) were assessed across all 73 studies. Twitter data was analysed in 34 studies [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ]; 23 studies examined YouTube [ 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , ...…”
Section: Resultsmentioning
confidence: 99%
“…In a thematic analysis of online mentions, Chenworth et al found that methadone had generated more extreme negative opinions then positive opinions, and stigma was the second most common theme mentioned online. 15…”
Section: Barriers To Implementation Safety Of Intraoperative Methadonementioning
confidence: 99%
“…Penelitian terdahulu menunjukkan bahwa sentimen merupakan pusat dari pelbagai kajian komunikasi dimana negativitas dan polarisasi dalam komunikasi politik hingga ulasan produk dan komentar memiliki pengaruh yang signifikan terhadap kondisi ekonomi, kehidupan sosial, politik, hingga isu-isu pembangunan yang terintegrasi dengan teknologi informasi [144]. Oleh sebab itu, aplikasi media sosial dirancang menggunakan metode serta algoritma yang dapat mendeteksi serta mengklasifikasikan tema atau topik pembahasan pengguna (user) di media sosial [145]. Hal ini menunjukkan pentingnya analisis metode dan penggunaan algoritma dalam menganalisis sentimen di media sosial.…”
Section: Analisis Sentimen DI Media Sosialunclassified